2015
DOI: 10.1111/psyg.12140
|View full text |Cite
|
Sign up to set email alerts
|

Increased dosage of donepezil for the management of behavioural and psychological symptoms of dementia in dementia with Lewy bodies

Abstract: We found that donepezil dose-dependently improved relapsing BPSD in these patients. Therefore, increasing the dosage of donepezil is a safe and effective treatment for patients with DLB who experience a relapse of BPSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Persons with dementia and reported suicidal ideation in this study more often were on anxiolytics and antidementia medication (acetylcholinesterase inhibitors and memantine). This was unexpected as anti-dementia medication is considered to improve neuropsychiatric symptoms (Finkel, 2004;Huang, Lin, Lane, & Tsai, 2012;Manabe, Ino, Yamanaka, & Kosaka, 2016;Olsen, Poulsen, & Lublin, 2005). One explanation may be that the prescription of these pharmaceuticals may vary depending on the stage of dementia, in favour of the mild and moderate stage.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with dementia and reported suicidal ideation in this study more often were on anxiolytics and antidementia medication (acetylcholinesterase inhibitors and memantine). This was unexpected as anti-dementia medication is considered to improve neuropsychiatric symptoms (Finkel, 2004;Huang, Lin, Lane, & Tsai, 2012;Manabe, Ino, Yamanaka, & Kosaka, 2016;Olsen, Poulsen, & Lublin, 2005). One explanation may be that the prescription of these pharmaceuticals may vary depending on the stage of dementia, in favour of the mild and moderate stage.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of previous meta-analyses, the present study indicated that donepezil was beneficial for DLB regarding cognitive function and global impression, but not in any other aspects. Recently published secondary analyses of donepezil suggest statistically significant advantages of donepezil over placebo regarding aspects of Behavioural and Psychological Symptoms of Dementia (BPSD), improvement of cognitive function and visual hallucinations (3638). Manabe et al (36) observed that 10 mg donepezil improved BPSD in DLB.…”
Section: Discussionmentioning
confidence: 99%
“… An open label study of 24 patients with DLB who had relapse of NPS after treatment with donepezil 5 mg found that NPI scores improved significantly for six of 10 behaviors after a dose increase to donepezil 10 mg. Importantly, visual hallucinations were significantly improved at weeks 2 (mean score, 2.80; P < 0.0001) and 4 (mean score 2.85; P < 0.0001) from baseline (mean score, 8.23) .…”
Section: Treatment For Dlbmentioning
confidence: 92%